Abdominal Myomectomy For The Treatment Of Symptomatic Uterine Fibroids - Malik, Tahreem; Zulfiqar, Taiba; Ali, Abid (Medical Science Journal for Advance Research, 2022)
Background: Fibroids are common problem for women in elderly reproductive age. Aim: The present study aimed at assessing abdominal myomectomy for the treatment of symptomatic uterine fibroids. Methodology: The present retrospective study was conducted from 22 June 2020 to 23 July 2021 at Mayo Hospital, Lahore. Females undergone abdominal myomectomy with age 30 to 50 years were included. The primary and secondary outcomes were defined and assessed to evaluate the procedure. Results: The findings indicate that 32 (62.74%) of the patients showed successful outcome for menorrhagia. On the other hand, 27 (50.94%) patients showed successful outcome for pain and 30 (60%) showed for mass effect. Conclusion: Abdominal myomectomy is an ideally applicable procedure for the removal of fibroids.